Antidiscrimination Law and Shared Prosperity : An Analysis of the Legal Framework of Six Economies and Their Impact on the Equality of Opportunities of Ethnic, Religious, and Sexual Minorities - Panter, Elaine; Primiani, Tanya; Hasan, Tazeen; Calderon Pontaza, Eduardo (World Bank, Washington, DC, 2017)
This paper looks at the structural marginalization of eth-nic, religious, and sexual minorities in six pilot economies (Bulgaria, Mexico, Morocco, the Netherlands, Tanzania, and Vietnam) and proposes a new methodology for collecting cross-country comparable data on antidiscrimination legal frameworks. The data cover six areas of law, ad-dressed by six indicators: (a) access to institutions, (b) access to education, (c) access to the labor market, (d) access to property, (e) access to public services and social protection, and (f) protection from hate crimes and hate speech. The laws, policies, and regulations presented fall under one of these indicators. For each, the paper attempts to identify the minority gap, the difference between the legal treatment of the ruling majority and that of the minority. Data were collected through two sources: first, standardized surveys submitted to ombudsman institutions, lawyers, academics, and civil society organizations; second, public government records on laws and regulations and data from international legal databases and human rights organizations. The idea driving the study is that institutional measures that hamper the access of ethnic, religious, and sexual minorities to the labor market and financial systems directly affect their economic performance and, as a consequence, represent a cost for the economy. Among the findings of the study is that antidiscrimination labor legislation is well developed in all six pilot economies, but many gaps still exist in access to property and in access to public goods and social services. The study also found that, of the three groups covered by the study, the least protected under the law are the sexual minorities. Although data from six economies cannot provide statistical evidence, findings suggest the need for further research. The authors hope to encourage a wider debate on the consequences of systematic discrimination against minorities and to help governments critically review their legal frameworks to ensure equal opportunities for all citizens, regardless of religion, ethnicity, gender identity or sexual orientation.